Using SAP System with English Use at Banking Corporate - Rezky Febrianti; Fatimah Hidayahni Amin; Riny Jefri (International Journal of Business English and Communication, 2024)
This study aimed at finding out the use of English in operating SAP System and the staff’ perception towards using such system in banking matters. The research was qualitative with a descriptive design. It was conducted at PT. Bank Rakyat Indonesia, Panakkukang Branch and was carried out for approximately 2 months. The selected respondents were 5 staff from different divisions who used SAP system to operate the banking matters. The study employed questionnaire and interview questions to collect the data. It was found that SAP system is a helpful tool for the bank because all activities are integrated using one software and it can accelerate processing and presenting more accurate data. It terms of familiarity, the staff needed some time to learn the system and to master English terms and vocabulary used in the system. However, the staff anticipated their understanding in using SAP system by following the standards that have been implemented in the bank.